Text-Based Inference Instruction for Elementary Grade Children with Reading Comprehension Difficulties: An Intervention Research - Viorel MIH; Codruţa MIH (Studia Universitatis Babes-Bolyai, 2024)
The current study investigated the effects of inference instruction on text-based inferences by third graders who are below average in reading comprehension but average in reading fluency and cognitive abilities. Text-based inferences occur when the preceding text has an identifiable causal antecedent. Participants were randomly assigned and attended twelve 30-minute sessions of the inferences training intervention. We have included strategies for integrating information from the text to improve reading comprehension skills. We provide an overview of how specific text-based instruction influences reading comprehension processes and outcomes and can lead to increased reading comprehension. The comparison of pretest and posttest results in the experimental group showed a significant gain in the following variables: generating inferences and providing arguments for using rules and constraints. Finally, we discuss how consideration of these potential sources of instruction has practical implications for designing and selecting instructional materials.